Potential Antioxidative Components in Azadirachta indica Revealed by Bio-Affinity Ultrafiltration with SOD and XOD - Min-Xia Fan; Gui-Lin Chen; Ming-Quan Guo (MDPI AG, 2022)
Azadirachta indica (A. indica) has been widely used due to its diverse pharmacological activities. However, there are currently few studies on its responsible antioxidant ingredients against superoxide dismutase (SOD) and xanthine oxidase (XOD). In this study, the antioxidant activities of A. indica were evaluated by a 2,2'-azinobis-(3-ethyl-benzthiazoline)-6-sulfonic acid) and ferric-ion-reducing antioxidant power method. Meanwhile, total polyphenol and flavonoid content were determined to reveal that they were the highest in ethyl acetate (EA) fraction. Next, compounds with the most antioxidant activity were screened out from EA fraction by bio-affinity ultrafiltration liquid chromatography-mass spectrometry (UF-LC-MS) with SOD and XOD. As a result, gallic acid, protocatechuic acid and (−)-epicatechin were identified as potential SOD ligands with relative binding affinity (RBA) values of 2.15, 1.78 and 1.61, respectively. Additionally, these three ligands could effectively interact with SOD in molecular docking with binding energies (BEs) ranging from −3.84 ± 0.37 to −5.04 ± 0.01 kcal/mol. In addition, carnosic acid exhibited a strong binding affinity to XOD with an RBA value of 2.05 and BE value of −8.24 ± 0.71 kcal/mol. In conclusion, these results indicated that A. indica might have good antioxidant activity and antigout potential, and the UF-LC-MS method is suitable and efficient for screening both SOD and XOD ligands from A. indica.